EARTHWORM DENSITY, BIOMASS AND VERMICOMPOST RECOVERY DURING AGRO-INDUSTRIAL WASTE TREATMENT - SANTHEBENNUR JAYAPPA VEERESH; JOGTTAPPA NARAYANA (International Journal of Pharma and Bio Sciences, 2013)
The primary purpose of this study was to assess influence of cow dung and a biodynamic microbial consortium (Jeevamrutha) on the earthworm density, biomass and vermicompost recovery during the treatment of papermill and sugar factory sludge into beneficial product. The maximum earthworm net biomass, vermicompost recovery and earthworm density found in agro-industrial waste treated with Jeevamrutha and cow dung respectively. Furthermore, there was a significant relationship between earthworm density and biomass with treatment groups. The inoculation of microbial consortia like Jeevamrutha and cow dung to organic substrates significantly enhances the earthworm density, biomass and highest recovery of vermicompost during vermicomposting process.